Public Private Partnership in National Highways (Six-Laning) Model Concession Agreement, April 2009 - Planning Commission (Planning Commission, 2009)
There is today a broad consensus that a sustained growth rate of about 8 to 9 per cent per annum is the minimum necessary if India is to eliminate poverty and achieve a quantum jump in the quality of life of its citizens. One of the preconditions for sustaining such a growth rate is the creation of world class infrastructure. The quality of our infrastructure, at present, simply will not allow the economy to reach the level of competitiveness needed to achieve 9 per cent growth in an open economy.
Planning Commission Government Of India
Planning Commission Government of India